The Compradazgo, Social Mobility and Power Relations of Free Mulattos. San Jose de Logrotio, Chile, 1780-1810 - Armijo-Reyes, A (CONSEJO SUPERIOR INVESTIGACIONES CIENTIFICAS-CSIC, 2020)
This article addresses compadrazgo or sponsorship between free mulattoes, a mechanism used to reinforce family and neighbourhood ties, but also as a form of support and/or legitimacy bestowing social prestige and building power relations in the town of San Jose de Logroho between 1780 and 1810. These relationships and links are documented in parish records, and in the wills and letters of freedom of slaves, whereby the use of social networks allows us to analyse the interpersonal ties between different sectors and social groups. The results indicate that the relationships between mulattoes and other individuals, groups and families involved the construction of social hierarchies among social peers, and permit analysis of how the strategies for ascent and social mobility operate.